2010
DOI: 10.1093/toxsci/kfq333
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response Assessment of Nephrotoxicity from a 7-Day Combined Exposure to Melamine and Cyanuric Acid in F344 Rats

Abstract: The intentional adulteration of pet food with melamine and derivatives, including cyanuric acid, has been implicated in the kidney failure and death of a large number of cats and dogs in the United States. Although individually these compounds present low toxicity, coexposure can lead to the formation of melamine cyanurate crystals in the nephrons and eventual kidney failure. To determine the dose-response for nephrotoxicity upon coadministration of melamine and cyanuric acid, groups of male and female F344 ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 13 publications
4
34
0
Order By: Relevance
“…Since the feed had been found to be free of CYA, MEL was likely converted to CYA by the gut bacteria (Seffernick et al, 2010;Wackett et al, 2002;Zheng et al, 2013) or, less likely, by the test animal's metabolism. Finding CYA in a pig dosed with MEL in this study is consistent with previous reports in rats and fish where crystals were found in a few of the animals dosed with MEL alone (Jacob et al, 2011;Reimschuessel et al, 2009;Stine et al, 2012;Stine et al, 2014).…”
Section: Residues Of Mel and Cya In Experimental Pigssupporting
confidence: 92%
“…Since the feed had been found to be free of CYA, MEL was likely converted to CYA by the gut bacteria (Seffernick et al, 2010;Wackett et al, 2002;Zheng et al, 2013) or, less likely, by the test animal's metabolism. Finding CYA in a pig dosed with MEL in this study is consistent with previous reports in rats and fish where crystals were found in a few of the animals dosed with MEL alone (Jacob et al, 2011;Reimschuessel et al, 2009;Stine et al, 2012;Stine et al, 2014).…”
Section: Residues Of Mel and Cya In Experimental Pigssupporting
confidence: 92%
“…The kidney tissue used in the current study was obtained from the same rats used to analyze the endpoints reported in Jacob et al (2011). Briefly, six-week-old F344 rats (6 males and 6 females per dose group) were fed ad libitum for seven days NIH-41 irradiated meal fortified with 0 (control), 7, 23, 69, 229, or 694 ppm melamine and cyanuric acid (co-exposure groups), 1388 ppm melamine only, or 1388 ppm cyanuric acid only.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we reported the effect of a seven-day combined exposure to melamine and cyanuric acid in F344 rats on body and kidney weights, kidney histopathology, and serum creatinine and blood urea nitrogen (BUN) levels (Jacob et al , 2011). We found that, while dietary exposure to 1388 ppm melamine or cyanuric acid failed to induce any significant changes on the endpoints analyzed, co-exposure to mixtures of 229 or 694 ppm melamine and cyanuric acid led to a decrease in body weight, enlarged and pale-yellow kidneys, multiple kidney tubular histopathological lesions, deposition of melamine cyanurate crystals in the renal tubules, and elevated serum creatinine and BUN levels compared to control animals.…”
Section: Introductionmentioning
confidence: 99%
“…Melamine is commonly used in the manufacture of laminates, houseware items, and flame retardants (Crews et al , 2006), while cyanuric acid is used as a chlorine stabilizer in swimming pool water and to prepare herbicides and dyes (Huthmacher and Most, 2003). Individually, MEL&CYA exhibit low toxicity (Choi et al , 2010; Jacob et al , 2011); however, the combined exposure to MEL&CYA results in the formation of melamine cyanurate crystals that can obstruct the nephron tubules and result in acute kidney injury (Dobson et al , 2008; Puschner et al , 2007). We reported previously that a 28-day daily dietary co-exposure to MEL&CYA induces dose-dependent nephrotoxicity in F344 rats, with males more sensitive than females (Gamboa da Costa et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%